Kemampuan Pemecahan Masalah Matematis Siswa Sekolah Dasar: Systematic Literature Review (SLR). - Riyanti, Dessy Az-Zahra Putri; Surya, Anesa (Universitas Sebelas Maret, 2025)
Mathematical problem-solving ability is an essential competency in elementary mathematics education to develop critical, logical, and systematic thinking skills. This study aims to comprehensively review the literature on the mathematical problem-solving abilities of elementary school students. The research employed a Systematic Literature Review (SLR) method following the PRISMA flow. Data were collected from articles in the Google Scholar database published between 2020 and 2025. The findings indicate that students tend to experience difficulties in the planning and evaluation stages of problem-solving, which are influenced by both internal and external factors. Effective strategies to improve problem-solving abilities include the use of the Realistic Mathematics Education (RME) model, concrete learning media, and personalized learning approaches by teachers. This study concludes that improving elementary school students' problem-solving abilities can be achieved through contextual learning strategies, engaging media, and adaptive teacher guidance. Kemampuan pemecahan masalah matematis merupakan kompetensi penting dalam pembelajaran matematika di sekolah dasar untuk membentuk pola pikir kritis, logis, dan sistematis. Penelitian ini bertujuan untuk mengkaji literatur tentang kemampuan pemecahan masalah matematis siswa sekolah dasar secara komprehensif. Metode penelitian yang digunakan adalah Systematic Literature Review (SLR) dengan mengikuti alur PRISMA. Data dikumpulkan dari artikel pada database Google Scholar yang diterbitkan antara tahun 2020-2025. Hasil kajian menunjukkan siswa cenderung mengalami kesulitan pada tahap perencanaan dan evaluasi pemecahan masalah yang dipengaruhi faktor internal maupun eksternal. Strategi yang efektif untuk meningkatkan kemampuan pemecahan masalah meliputi penggunaan model Realistic Mathematics Education (RME), media konkret, serta pendekatan pembelajaran personal oleh guru. Simpulan dari penelitian ini adalah bahwa peningkatan kemampuan pemecahan masalah siswa sekolah dasar dapat dilakukan melalui penerapan strategi pembelajaran kontekstual, penggunaan media yang menarik, dan pendampingan guru yang adaptif.